2021
DOI: 10.1016/j.sjbs.2021.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Dieckol exerts anticancer activity in human osteosarcoma (MG-63) cells through the inhibition of PI3K/AKT/mTOR signaling pathway

Abstract: Background Osteosarcoma (OS) is the most common malignant bone cancer with more metastasis and increased occurrence in children and teen-agers and being responsible for more number of morbidity and mortality worldwide. Objective The current exploration was planned study the in vitro anticancer actions of dieckol against human OS MG-63 cells via PI3K/AKT/mTOR signaling inhibition. Methodology The cytotoxicity of diec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 50 publications
3
10
0
Order By: Relevance
“…Later, 32 and 50 μg/ml of DKL and 0.5 μg/ml of PTX were given to HCT‐116 cells and continued for another 24 h. After that, each well received 10 μl of DCFH‐DA stain, which was left to sit for an hour. After treatment, ROS levels in the HCT‐116 cells were observed under a fluorescence microscope [ 25,26 ] , or rhodamine‐123 for the evaluation of ΔΨ m by exploratory investigation under the inverted fluorescence microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Later, 32 and 50 μg/ml of DKL and 0.5 μg/ml of PTX were given to HCT‐116 cells and continued for another 24 h. After that, each well received 10 μl of DCFH‐DA stain, which was left to sit for an hour. After treatment, ROS levels in the HCT‐116 cells were observed under a fluorescence microscope [ 25,26 ] , or rhodamine‐123 for the evaluation of ΔΨ m by exploratory investigation under the inverted fluorescence microscope.…”
Section: Methodsmentioning
confidence: 99%
“… Liu et al (2017) reported that apatinib as a highly selective VEGFR2 antagonist which, has a promising antitumoral effect by the growth inhibition of osteosarcoma cells in vitro and in vivo through apoptosis, cell cycle arrest, and autophagy ( Liu et al, 2017 ). Zhang et al (2021) evaluated that the effective inhibition of dieckol in the PI3K/AKT/mTOR signaling on the MG-63 cells ( Zhang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“… Bahuguna et al (2017) reported that MTT assay for cytotoxicity evaluation has many advantages in especially its effectiveness and simplicity, which make it more suitable to assess the anti-cancer potential of any test samples at preliminary levels ( Bahuguna et al, 2017 ). Zhang et al (2021) demonstrated the cytotoxic effect of dieckol in human osteosarcoma MG-63 cells using MTT assay ( Zhang et al, 2021 ). Liu et al (2015) revealed that the combination of ZD6474 and celecoxib had a stronger antiproliferative effect in human osteosarcoma cells (MG-63) through MTT assay ( Liu et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Bcl-2 and Bax were the downstream target proteins of the PI3K/AKT signaling pathway. 25 To further explore the relationship between apoptosis and liver damage induced by APAP, western blot analysis was performed to assess the expression levels of Bcl-2 and Bax. We found that the PI3K/ AKT pathway APAP-induced liver injury was successfully inhibited after 7 days of DHM pretreatment, and the protein levels of Bax and Bcl-2 were close to that of the control group.…”
Section: Discussionmentioning
confidence: 99%